Cost-effectiveness analysis of active psoriatic arthritis treatment with ixekizumab in adult patients in Russian Federation health care system - E. A. Pyadushkina; E. V. Derkach; M. Yu. Frolov; V. A. Rogov; A. S. Salasyuk (Современная ревматология)
Objective: to evaluate the economic impact of the use of various biologic disease-modifying antirheumatic drugs (bDMARDs) from the group of inhibitors of interleukins (iIL) 12/23 and iIL17 in adult patients with psoriatic arthritis (PsA) with insufficient response to therapy with TNFα inhibitors (TNFα inhibitors).Patients and methods. A Microsoft Excel model has been developed, it allows to calculate the average cost of treatment of 1 patient with PsA who needs a second-line bDMARD from the iIL12/23 or iIL17 group. Only direct medical costs (drug costs) were considered. Cost minimization analysis and budget impact analysis were carried out.Results and discussion. The results of a network meta-analysis demonstrate no statistically significant differences in efficacy and safety between ixekizumab (IXE) and secukinumab (SEC) and superiority SEC over ustekinumab when used in adult patients with active PsA with insufficient response to or intolerance of previous therapy with synthetic disease-modifying antirheumatic drugs or TNFα inhibitors. The analysis of cost minimization showed that the total cost of 1 patient managing for 1 year using IXE is 26% lower than treatment with SEC: on a 2 year horizon, the difference is 27%. Analysis of the impact on the budget revealed that on the horizon of 1 year the simulated distribution will lead to budget savings of 16,796,131 rubles, which will allow additional treatment of 17 patients with IXE, after 2 years the budget savings will amount to 39,289,373 rubles, which will allow to treat additionally 52 patients. The sensitivity analysis confirmed the robustness of the study results.Conclusion. Thus, in adult patients with PsA requiring second-line bDMARDs, the use of IXE is more effective than the use of SEC and provides reduction in direct medical costs. The use of IXE will not have a significant impact on costs under the State Guarantee Program, but it can increase the availability of bDMARDs in patients with active PsA who have not responded to the previous therapy, without increasing the budget.